circular no. 28/2015 regarding application of the amendments introduced to the income tax law = كتاب دوري رقم 28 لسنة 2015 بشأن تطبيق التعديلات التي تمت على قانون الضريبة على الدخل - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
circular no. 28/2015 regarding application of the amendments introduced to the income tax law promulgated by law no. 96 of the year 2015 كتاب دوري رقم 28 لسنة 2015 بشأن تطبيق التعديلات التي تمت على قانون الضريبة على الدخل